2014
DOI: 10.1177/0886260514539843
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, Physical, and Sexual Abuse in Addicted Patients Who Undergo Treatment

Abstract: This study explored the prevalence of a history as victims of abuse among patients who sought outpatient treatment for drug addiction. A sample of 252 addicted patients was assessed. Information was collected on the patients' lifetime history of abuse (psychological, physical, and/or sexual abuse), sociodemographic factors, consumption factors, psychopathological factors, and personality variables. Drug-addicted patients who present a lifelong history of abuse were compared with patients who were not abused. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 45 publications
7
25
0
2
Order By: Relevance
“…The most frequent type of abuse reported was psychological, followed by physical abuse and sexual abuse. These figures complement the results found in previous studies, which showed higher rates of abuse in women than in men (Fernández-Montalvo et al, 2015;Sacks et al, 2008;Schneider et al, 2008).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The most frequent type of abuse reported was psychological, followed by physical abuse and sexual abuse. These figures complement the results found in previous studies, which showed higher rates of abuse in women than in men (Fernández-Montalvo et al, 2015;Sacks et al, 2008;Schneider et al, 2008).…”
Section: Discussionsupporting
confidence: 94%
“…This problem especially affects addicted women, whose rates of lifetime abuse (psychological, physical, and sexual) are significantly higher than those observed in men (Fernández-Montalvo, López-Goñi, & Arteaga, 2015;Sacks, McKendrick, & Banks, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…This remarkably high level of violence against impoverished women is consistent with studies in multiple geographic areas (Bonugli et al, 2013; Bourgois et al, 2004; Galano et al, 2013; Riley et al, 2014; Tutty et al, 2013; Wenzel et al, 2006), suggesting the ongoing recognition of this public health problem and the lack of an effectual response. Results presented here and elsewhere suggest that continued violence against impoverished women not only compromises health and increases emergency department use (Doran et al, 2014), it also increases the risk of subsequent drug use (ARR = 4.56; 95% CI: 1.93–10.76; Table 2) and increases the severity of addiction (Fernandez-Montalvo et al, 2014a). …”
Section: Discussionmentioning
confidence: 70%
“…Among patients with drug addiction problems, those presenting with suicidalrelated behaviours appear to have suffered more from lifetime abuse. Similarly, patients who sought treatment for substance use disorder with a history of lifetime abuse show higher rates of suicidal ideation and/or suicide attempts (Fernández-Montalvo, López-Goñi, & Arteaga, 2015;Hung et al, 2013;Roy, 2010;Roy & Janal, 2007;Trout, Hernandez, Kleiman, & Liu, 2017;Vaszari et al, 2011). For example, in a study by Fernández-Montalvo et al (2015), the rate of suicidal ideation in a sample of 115 patients in treatment for addictions problems with histories of any type of lifetime abuse (psychological, physical and/or sexual) reached 48.8%, and the rate of suicide attempts was 21.3%.…”
Section: Introductionmentioning
confidence: 99%